Factores de riesgo que influyen en el cáncer cérvico uterino en las pacientes que acuden al Hospital del IESS de Santo Domingo, 2015 - Salinas Tapia, Fabiola María (2015)
Cervical cancer is a serious public health problem globally and nationally, diagnosing over 400,000 new cases each year and occurring about 300 thousand deaths per year. Is of great importance to determine the causes and risk factors this pathology. This cancer is affecting more strongly to women of reproductive age has increased in recent decades. Cervical cancer is a product of biological risk factors and socio-cultural character disease. Factors associated, more consistently, with cervical cancer is infection with human papillomavirus (HPV), sexual habits (history of two or more sexual partners or the onset of sexual life at an early age), called reproductive risk factors in women (as multiparity, consumptiontype hormonal contraceptives, family history of Cervical Cancer) and harmful habits like smoking. The aim is to identify risk factors, knowledge and prevention measures about cervical cancer that women of childbearing age. The study is descriptive cross, with technical survey, with a series of questions that was applied to 100 women of childbearing age, which allowed an analysis of the degree of knowledge we have about cervical cancer, factors risks and prevention measures. KEYWORDS: FACTORS, RISK, CERVICAL CANCER, KNOWLEDGE, PREVENTION, MORTALITY